(untitled) (Research, Society and Development, 2020)
ML-SAI is a pedagogical model developed for activities with mobile devices, based on the theory of the Inverted Classroom (IC). The purpose of this article is to deepen the understanding of the benefits and challenges of using the ML-SAI pedagogical model. For this, we used the students’ own smartphones and digital technology resources, such as YouTube, WhatsApp, among others. Data collection was performed through observation made by the researcher, collecting the perceptions of the students and teachers involved, through the online questionnaire and through the students’ records in the Edmodo virtual environment. ML-SAI emerges as an innovative proposal for the use of mobile digital technologies, supported by IC educational practices, helping to renew and transform the traditional form of teaching and learning, adapting to the characteristics of today’s technological society.